2018
DOI: 10.1080/02656736.2018.1492027
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific CD8-positive T cell-mediated antitumor immunity is implicated in the antitumor effect of local hyperthermia

Abstract: CD8-positive T cell-mediated antitumor immunity significantly contributes to the antitumor effect of LH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Recently, several groups have reported the combined effects of local HT with ICI. Ando et al reported that the addition of C4 to local HT at 42.5 C for 60 min in a water bath did not significantly inhibit the growth of HT tumors compared with local HT monotherapy in EL-4 lymphoma-bearing mice [32]. Chao et al reported that magnetic HT at 50 C for 10 min with PD-L1 blockade and poly (lactic-co-glycolic) acid R837 nanoparticles induced both local and abscopal effects in back skin tumors in B16-bearing mice [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups have reported the combined effects of local HT with ICI. Ando et al reported that the addition of C4 to local HT at 42.5 C for 60 min in a water bath did not significantly inhibit the growth of HT tumors compared with local HT monotherapy in EL-4 lymphoma-bearing mice [32]. Chao et al reported that magnetic HT at 50 C for 10 min with PD-L1 blockade and poly (lactic-co-glycolic) acid R837 nanoparticles induced both local and abscopal effects in back skin tumors in B16-bearing mice [33].…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding heat and the immune system varies largely depending on the heating methods and treatment durations used; what is well known, however, is that controlled, localized heat can elicit a systemic anti-tumor immune response. [200][201][202][203] The evidence associated with this immune stimulation strongly suggests an induction of dendritic cell (DC) maturation and cross-presentation to CD8 + T cells, while other findings hint at a heightened cytotoxicity profile of NK cells. [200,204]…”
Section: Localized Heat and The Immune Systemmentioning
confidence: 99%
“…[212,213] DC can then home to the draining lymph node and cross-present tumor antigens to CD8 + T cells, enabling their effector function to expand and migrate to the tumor site and elicit a cytotoxic response. [201,214] Numerous in vivo studies have confirmed this adaptive immune response by treating tumor-bearing rodents with moderate hyperthermia and then re-challenging them with the same tumors at a later time to observe if a memory response exists. Some notable examples of this response are discussed next.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…HT elicits innate and adaptive immune responses which may enhance its treatment effects [3,42,43]. Studies have found that HT may increase the cytotoxic activity of natural killer (NK) and CD8þ T cells against tumor cells [44,45]. Preclinical studies have demonstrated that immunotherapy following HT may enhance antitumor immune responses [46][47][48][49].…”
Section: Ht and Immunomodulationmentioning
confidence: 99%